HUBUNGAN ANTARA NEUROLOGICAL SOFT SIGN DENGAN INTELLIGENCE QUOTIENT PADA ANAK USIA 8-9 TAHUN - Lani Satiyani; Siti Aminah; Paulus Anam Ong (NEURONA, 2018)
ASSOCIATION BETWEEN NEUROLOGICAL SOFT SIGN AND IQ IN 8-9 YEARS OLDABSTRACTIntroduction: Neurological soft signs (NSS) are common findings in developing children and tend to disappear as the child grows up. Their persistence into later years correlate with motor and cognitive development disturbance.Aim: To examine the relationship between NSS and intelligence quotient (IQ) in 8-9 years old children in Bandung.Methods: This analytic observational case control study was conducted in elementary school children in Bandung from May to July 2017. The case group is defined as subject with NSS score ≥7, while controls are those with NSS score <7. Neurological soft signs was assessed with Gillberg method and IQ (original, full scale, performance, and performance) was assessed with Wechsler Intelligence Scale for Children (WISC)-III. Statistical analyses were performed to find the relationship between NSS and IQ score.Results: Sixty eight subjects, majority were male (61.76%) with median age 8.8 (8-9) years old took part in the study. Case group had lower mean score of IQ significantly. Subjects with higher NSS score had risk of having having lower full scale and performance IQ 4.94 and 11.20 times compared to subjects with lower NSS. There was an inverse correlation between NSS score and organizational IQ.Discussion: Subjects retaining neurological soft sign have the possibility of having lower IQ compared to subjects without NSS.Keyword: Children, intelligence quotient, neurological soft signABSTRAKPendahuluan: Neurological soft sign (NSS) sering ditemukan pada anak dalam masa tumbuh kembang dan menghilang dengan bertambahnya usia. Menetapnya NSS pada usia tertentu berhubungan dengan gangguan perkembangan motorik dan fungsi kognisi.Tujuan: Mengetahui hubungan antara NSS dengan nilai intelligence quotient (IQ) anak usia 8-9 tahun di kota Bandung.Metode: Penelitian observasi analitik dengan desain kasus kontrol pada anak sekolah dasar di kota Bandung pada bulan Mei sampai Juli 2017. Kelompok kasus adalah subjek dengan skor NSS ≥7, sedangkan kontrol adalah subjek dengan skor NSS <7. Pemeriksaan NSS menurut metode Gillberg, sedangkan kecerdasan anak berdasarkan IQ menggunakan Wechsler Intelligence Scale for Children (WISC)-III. Dilakukan uji statistik untuk mencari hubungan antara NSS dengan IQ.Hasil: Didapatkan 68 subjek yang mayoritas laki-laki (61,76%) dengan median usia 8,8 (8-9,9) tahun. Kelompok kasus memiliki nilai rerata IQ lebih rendah dibandingkan dengan kontrol secara bermakna. Subjek dengan skor NSS tinggi mempunyai kemungkinan sebesar 4,94 dan 11,20 kali untuk memiliki skor full scale IQ (FSIQ) dan performance IQ (PIQ) yang lebih rendah dibandingkan subjek dengan NSS rendah. Terdapat korelasi negatif yang bermakna antara skor NSS dengan organizational IQ (OIQ).Diskusi: Subjek dengan neurological soft sign yang menetap memiliki kemungkinan nilai IQ yang lebih rendah dari pada yang tanpa gejala NSS.Kata kunci: Anak, intelligence quotient, neurological soft sign